Politeness Strategies for Criticizing in the Japanese Workplace: A Pragmatic Study - Santoso, Teguh; Slamet; Miftah Nugroho (Universitas Airlangga, 2024)
Criticism plays a crucial role in improving individual and team performance and addressing shortcomings in workplace processes. However, the way criticism is delivered significantly impacts how it is received. This study examines politeness strategies in delivering criticism in Japanese workplaces, drawing on Nguyen's (2005) politeness theory. Using the Discourse Completion Test (DCT) method, the study involved 25 students from the Japanese Literature Program at Universitas Ngudi Waluyo who work in Japan. The findings reveal that direct criticism is rarely used in Japanese workplaces as it risks disrupting wa (harmony) and causing embarrassment, particularly in formal or peer relationships. Direct criticism is employed only in urgent situations or within hierarchical relationships, characterized by explicit, firm language aimed at immediate correction. Conversely, indirect criticism is more prevalent, utilizing linguistic strategies such as suggestions, invitations, or questions to maintain politeness and relational stability. From a sociopragmatic perspective, cultural norms, status hierarchies, and social contexts influence the choice of criticism strategies. From a pragmalinguistic perspective, subtle and implicit linguistic elements are effective in preserving harmony and avoiding confrontation. The study concludes that the success of delivering criticism relies on balancing communicative effectiveness with maintaining harmonious workplace relationships.